Inoculation of Native Arbuscular Mycorrhizae and Bacillus subtilis Can Improve Growth in Vegetable Crops - Gebreslassie, Sara; Jida, Mulissa; Puente, Mariana Laura; Covacevich, Fernanda; Belay, Zerihun (Wiley, 2025)
Arbuscular mycorrhizal fungi (AMF) and some rhizobacteria are known as plant growth-promoting microorganism (PGPM) as they play significant roles in improving soil fertility structure, plant nutrition, growth, and health. However, little is known about the PGPM potential of AMF and rhizobacteria native to the Rift Valley and highland regions of Ethiopia. Hence, this study aimed to investigate the PGPM effect of single and co-inoculation of AMF and the Bacillus subtilis ALCR46 strain, on tomato (Lycopersicum esculentum L.), onion (Allium cepa L.), and squash (Cucurbita pepo L.) plants. The experimental setup was a randomized complete block design with three replications of the following treatments: (i) inoculation with a consortium of AMF, (ii) co-inoculation with a consortium of AMF and the Bacillus subtilis, (iii) inoculation with Rhizophagus clarus, (iv) co-inoculation with R. clarus and B. subtilis, (v) inoculation with B. subtilis, (vi) plants without inoculation (negative control), and (vii) plants treated with chemical fertilizer (positive control). Plants were maintained in a greenhouse for 60 days, and after harvest, plant growth parameters, percentage of AMF root colonization, and spore number were analyzed. The result shows that the growth of crops significantly increased by co-inoculation with the consortium of AMF and B. subtilis. AMF spore density and root colonization rate were also increased in co-inoculated plants. Highest root colonization, spore number, and mycorrhizal dependency were observed in A. cepa. Our results suggest that there is a synergistic effect between the AMF and B. subtilis ALCR46, and between AMF inoculants. However, the application of present findings under field conditions is required to be confirmed by further studies.